The Development of HOTS Questions Based on Ethnomathematics to Measure Students' Mathematical Problem-Solving Abilities - Harahap, Sinar Depi; Ahmad, Marzuki; Pasaribu, Joni Winra (LPPM Universitas Pendidikan Mandalika, 2024)
The research aims to develop ethnomathematics-based Higher Order Thinking Skills (HOTS) questions to measure students' problem-solving abilities. This research uses a research and development (R&D) method with an ADDIE model, which consists of five stages, i.e., analysis, design, development, implementation, and evaluation. The subjects in this research were 30 class VIII students at SMP Negeri 1 West Sorkam. Research instruments include expert validation questionnaires, student response questionnaires and tests of students' mathematical problem-solving abilities. The research data were analyzed using quantitative descriptive methods by determining the average achievement value of the products developed. The experts' assessment shows that the product developed has a score of 84.6 with the criteria